Factors That Influence Behavioral Intention Users of The E-Commerce Application Shopeefood in Jakarta - Ardhea Larasati; Irma Satya Indriyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to examine the influence of Attitude, Subjective Norms, Perceived Behavioral Control, and Trust on the Behavioral Intention of ShopeeFood users in Jakarta. The research employs a descriptive and causal approach. Data were collected through an online questionnaire distributed to respondents who are active ShopeeFood users and meet specific criteria. The sampling technique used was purposive sampling with a total of 170 respondents. Variables were measured using a five-point Likert scale, and the data were analyzed using multiple linear regression with statistical software. The results show that Subjective Norms and Trust have a significant influence on Behavioral Intention, while Attitude and Perceived Behavioral Control do not have a significant effect .